The Missisauga to Logan Canyon formation transition: Early Cretaceous dinoflagellate cyst bioevents from Panuke B-90 well, Scotian Margin (offshore Atlantic Canada) - Correia, Vânia; Fensome, Robert A.; Dafoe, Lynn T.; MacRae, R. Andrew; Williams, Graham L. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
Due to the rapid evolution of dinoflagellates, their fossil cysts are reliable age markers in the Mesozoic and Cenozoic. The Scotian Margin contains a well-developed succession of Mesozoic strata that accumulated during the opening of the North Atlantic Ocean. We focus on Lower Cretaceous conventional cores 4 to 13 from the Panuke B-90 well, which yield significant dinoflagellate cyst (dinocyst) assemblages. Four intervals from the section are defined based on associated lithologies, and in each interval the palynological assemblages broadly reflect changes in paleoenvironmental setting. Dinocyst occurrences and associated key bioevents are used to refine age. In the marginal marine Interval 1, the co-occurrence of Odontochitina operculata and Tenua anaphrissa and the first occurrence (FO) of Pseudoceratium retusum indicate an early Barremian age. Above the dominantly terrestrial Interval 2, the FOs of Palaeoperidinium cretaceum and Cerbia tabulata suggest a late Barremian age for the terrestrial to marine Interval 3. Near the boundary between Interval 3 and marine Interval 4, a Cerbia tabulata acme and the FO of Aptea cf. polymorpha, as well as the last occurrence (LO) of Muderongia microperforata, confirm an early Aptian age. Accordingly, the Upper Member of the Missisauga Formation is Barremian to lower Aptian and the overlying Naskapi Member of the Logan Canyon Formation is lower Aptian; the presence of the early Aptian ammonite Deshayesites provides further age constraint. The key dinocyst bioevents f rom Panuke B-90 conventional cores are an important contribution to the ongoing Mesozoic event-stratigraphic framework for the Scotian Margin.